2014
DOI: 10.1080/00036846.2014.894630
|View full text |Cite
|
Sign up to set email alerts
|

Estimating bivariate yield distributions and crop insurance premiums using nonparametric methods

Abstract: Modelling crop yield distribution is crucial in crop insurance premium setting. The correlation between different crop yields due to rotations or systemic risks requires estimation of joint yield distribution for multiple crops. In this article, we apply a nonparametric method to estimate bivariate yield distributions using farm-level yield data of wheat and corn in Shandong Province in China. Then, the simulated yields are used to evaluate the expected indemnity of one traditional and one hypothetical crop in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…For example, yield insurance systems could be set up in order to compensate high yield losses for risky crops 24 25 26 . Such systems require accurate estimations of yield anomaly distributions in order to derive reliable risk premiums 17 18 19 20 . Our study indicates that, in Europe, risk premiums are likely to be higher for most of the legume species compared to major non-legume species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, yield insurance systems could be set up in order to compensate high yield losses for risky crops 24 25 26 . Such systems require accurate estimations of yield anomaly distributions in order to derive reliable risk premiums 17 18 19 20 . Our study indicates that, in Europe, risk premiums are likely to be higher for most of the legume species compared to major non-legume species.…”
Section: Discussionmentioning
confidence: 99%
“…A rigorous analysis of such risks is crucial for decision makers to define and promote efficient agro-environmental policies for grain legumes in Europe. An accurate estimation of yield loss distribution is also a key element for developing insurance systems against yield loss 17 18 19 20 . To date, only qualitative information from either country-level surveys or expertize is available on this topic 12 13 14 15 16 21 .…”
mentioning
confidence: 99%
“…Hou et al (2011) used the subjective perception of risk and loss as the proxy of risk aversion during testing adverse selection of crop insurance in northern China. Different contract design may also influent farmers' purchase behavior, Zheng et al (2014) shown that the hypothetical two-crop insurance contract can be more affordable to farmers than traditional individual crop insurance contracts.…”
Section: Risk Aversionmentioning
confidence: 99%
“…Many insurance companies with the support of governments deliver insurance programs. Several studies regarding Chinese agricultural insurance have been published (Zhong et al 2007;Turvey and Kong 2010;Boyd et al 2011;Okhrin et al 2013;Zheng et al 2014). However, none has addressed the information asymmetry issues mentioned above.…”
Section: Hog Production and Insurance In Chinamentioning
confidence: 99%